2015
DOI: 10.1186/s13064-015-0052-8
|View full text |Cite
|
Sign up to set email alerts
|

An emerging role for prdm family genes in dorsoventral patterning of the vertebrate nervous system

Abstract: The embryonic vertebrate neural tube is divided along its dorsoventral (DV) axis into eleven molecularly discrete progenitor domains. Each of these domains gives rise to distinct neuronal cell types; the ventral-most six domains contribute to motor circuits, while the five dorsal domains contribute to sensory circuits. Following the initial neurogenesis step, these domains also generate glial cell types—either astrocytes or oligodendrocytes. This DV pattern is initiated by two morphogens—Sonic Hedgehog release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 158 publications
0
10
0
Order By: Relevance
“…In the p419 mutant line in which the C1 turning angle of the startle response is dramatically increased (165% of wild type siblings; Table 1 and Fig 1L–1P and S3 Video ), we identified a missense mutation in the coding sequence of PR domain containing 12b ( prdm12b ). Prdm proteins are transcription factors, and several family members have been shown to play roles in nervous system development [ 43 ]. Zebrafish prdm12b was previously identified in a screen for genes that express in the nervous system [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the p419 mutant line in which the C1 turning angle of the startle response is dramatically increased (165% of wild type siblings; Table 1 and Fig 1L–1P and S3 Video ), we identified a missense mutation in the coding sequence of PR domain containing 12b ( prdm12b ). Prdm proteins are transcription factors, and several family members have been shown to play roles in nervous system development [ 43 ]. Zebrafish prdm12b was previously identified in a screen for genes that express in the nervous system [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of lateral motor column (LMC; FOXP1), dorsal interneuron/lateral motor column marker (LHX1) and medial motor column markers (MMC; LHX3) found that all PNP conditions preferentially generated LHX1 + / TUJ + cells although did not express ISL1 (Figure 8B,D). The prescense of LHX1 + /ISL1 − positive neurons, suggests neurons may be lateral LMC (LHX1 + /ISL2 + ), interneurons of the p2-dp2 domains or medial LMC which no longer express early motor neuron markers (Francius and Clotman, 2014, Zannino and Sagerström, 2015) (Figure 8B). Few cells were found to express LHX3 indicating cells preferentially differntate MMC motor neurons (Figure 8C).…”
Section: Resultsmentioning
confidence: 99%
“…Prdm proteins are transcription factors, and several family members have been shown to play roles in nervous system development [43]. Zebrafish prdm12b was previously identified in a screen for genes that express in the nervous system [44].…”
Section: Prdm12b Regulates Development Of V1 Interneurons and Regulatmentioning
confidence: 99%